Small Hydro-power Plants in Kenya: A Re view of Status, Challenges and Future Prospect - Mbaka, John Gichimu; Mwaniki, Mercy W. (Materials and Energy Research Center (MERC) & Iranian Association of Chemical Engineers (IAChE), 2016)
Small Hydro-power Plants (SHP) are important sources of electricity in many countries. However, little is known about SHP in Kenya. This paper reviews the status, challenges in implementation of SHP and prospects for future development of SHP in Kenya. The paper shows that SHP has not yet fully utilized the available hydro-power potential. The challenges associated with SHP development should be addressed to realize its full hydro-power generation potential in the future
Keywords: Electricity; Energy; Small Hydro‐Power Plant (SHP); Kenya